2020
DOI: 10.1002/jcp.29995
|View full text |Cite
|
Sign up to set email alerts
|

YEATS2 is a target of HIF1α and promotes pancreatic cancer cell proliferation and migration

Abstract: Hypoxia is involved in the development of pancreatic cancer (PC). The responses of hypoxia-associated genes and their regulated mechanisms are largely unknown. In this study, through bioinformatic analysis and quantitative real-time polymerase chain reaction, the YEATS domain containing 2 (YEATS2) was determined to be a key hypoxia-associated gene. It was increased in PC cells under hypoxia, upregulated in PC tissues, and predicted poor outcome. YEATS2 inhibition decreased the proliferation and migration of PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 27 publications
2
22
0
Order By: Relevance
“…Similarly, Overexpression of hydroxyproline via EGLN/HIF1A is associated with distant metastasis in PC [31]. Similarly, our early study also demonstrated that YEATS2 directly targets HIF1α which promotes PC cellS proliferation and mobility [32]. In the present study, we provided the rst evidences that FUT11 was a novel target gene of HIF1α, which involved in the biology function mediating by HIF1α under hypoxia.…”
Section: Discussionsupporting
confidence: 65%
“…Similarly, Overexpression of hydroxyproline via EGLN/HIF1A is associated with distant metastasis in PC [31]. Similarly, our early study also demonstrated that YEATS2 directly targets HIF1α which promotes PC cellS proliferation and mobility [32]. In the present study, we provided the rst evidences that FUT11 was a novel target gene of HIF1α, which involved in the biology function mediating by HIF1α under hypoxia.…”
Section: Discussionsupporting
confidence: 65%
“…Similarly, overexpression of hydroxyproline via EGLN/HIF1A is associated with distant metastasis in PC (30). Similarly, our previous study also demonstrated that YEATS2 directly targets HIF1a which promotes PC cell proliferation and mobility (31).…”
Section: Discussionsupporting
confidence: 52%
“…The YEATS domain containing 2 (YEATS2) protein is a selective histone crotonylation reader that regulates the activity of histone deacetylases. HIF-1α increases YEATS2 expression via binding to its hypoxia response element (HRE) to promote the proliferation and migration of PC cells under hypoxia [145]. Moreover, HIF-1α mediates transcriptional activation of urokinase-type plasminogen activator receptor (uPAR) and uPAR-dependent angioinvasion, which is critical for hypoxia-induced metastasis [146].…”
Section: Emt Invasion Migration and Metastasis Under Hypoxiamentioning
confidence: 99%